Living Matter: The Preservation of Biological Materials in Contemporary Art : An International Conference Held in Mexico City, June 3–5, 2019 - Roth, Kendra; Rivenc, Rachel (Book collections on Project MUSE., 2022)
"This is the first book to provide a comprehensive overview of the conservation of biological materials used in contemporary art"--